Development of a methodology for large-scale production of prions for biological and structural studies - Concha-Marambio, Luis; Wang, Fei; Armijo, Enrique; Gorski, Damian; Ramirez, Frank; Scowcroft, Andrew; Pritzkow, Sandra; Soto, Claudio (Frontiers in Molecular Biosciences, 2023)
Prion diseases are a group of infectious neurodegenerative diseases produced by the conversion of the normal prion protein (PrPC) into the disease-associated form (PrPSc). Extensive evidence indicate that the main or sole component of the infectious agent is PrPSc, which can replicate in affected individuals in the absence of nucleic acids. However, the mechanism of PrPC-to-PrPSc conversion remains elusive, which has been attributed to the lack of sufficient structural information of infectious PrPSc and a reliable system to study prion replication in vitro. In this article we adapted the Protein Misfolding Cyclic Amplification (PMCA) technology for rapid and efficient generation of highly infectious prions in large-scale. Murine prions of the RML strain were efficiently propagated in volumes up to 1,000-fold larger than conventional PMCA. The large-scale PMCA (LS-PMCA) procedure enabled to produce highly infectious prions, which maintain the strain properties of the seed used to begin the reaction. LS-PMCA was shown to work with various species and strains of prions, including mouse RML and 301C strains, hamster Hyper prion, cervid CWD prions, including a rare Norwegian CWD prion, and human CJD prions. We further improved the LS-PMCA into a bioreactor format that can operate under industry-mimicking conditions for continuous and unlimited production of PrPSc without the need to keep adding brain-derived prions. In our estimation, this bioreactor can produce in 1d an amount of prions equivalent to that present in 25 infected animals at the terminal stage of the disease. Our LS-PMCA technology may provide a valuable tool to produce large quantities of well-defined and homogeneous infectious prions for biological and structural studies.